Comparison of the Rate of Verbal Oral Movements in Healthy Younger and Older Native Speakers of Persians - Shiva Ebrahimian dehaghani; Atefeh Hoseinzadeh Mofrad; Jalal Bakhtiyari (Shiraz University of Medical Sciences, 2021)
Background: Normal aging is associated with many changes in speech-producing elements that can influence the articulators' ability to produce sounds quickly and precisely. To diagnose any motor problems in the oral area, it is necessary to obtain numerical oral motor performance rates in normal individuals. According to previous studies, quantitative measures of Oral diadochokinesis (DDK) vary across different cultures, languages, and ages. However, little research has been conducted in Persian native speakers to evaluate normal DDK in different age groups. Therefore, this study aimed to determine and compare DDK indicators in healthy young and older Persian native speakers. Methods: The participants were 105 healthy young and older individuals (56 women and 49 men) with the age range18-40, 60-80, and >80 years. Each subject was asked to repetitively express the syllables 15 times, and the sequence /pataka/ 10 times. Mann-Whitney and independent-sample t-tests were applied to show the differences, respectively between and within age groups. Results: The significant difference was revealed between young and older groups in performance in all tasks (p=0.00). In younger participants, increasing age correlated significantly with increasing time needed to produce /ta/ (p=0.04) and /ka/ (p=0.01) syllables. Also, the rate variation decreased as the point of articulation moved backward in the vocal tract for /ta/ and /ka/ production in both the older (p=0.6) and younger group (p=0.4). Conclusion: The results of this study can also help clinicians to document differences in the articulation rate between older and younger people and diagnose abnormal oral motor rates.